2016
DOI: 10.1063/1.4940708
|View full text |Cite
|
Sign up to set email alerts
|

Superior endurance performance of nonvolatile memory devices based on discrete storage in surface-nitrided Si nanocrystals

Abstract: The surface-nitrided silicon nanocrystals (Si-NCs) floating gate nonvolatile memory (NVM) devices were fabricated by 0.13 μm node CMOS technology. The surface-nitrided Si-NCs were formed in-situ by low-pressure chemical vapor deposition and followed by nitridation treatment in NH3 ambient. It is found that the nitridation treatment not only enhances the control effect of gate voltage on channel carriers by passivation of the Si-NCs surface defects but also suppresses releasing of the stored carriers among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In our previous work, we reported that the surface-nitrided Si-NC NVM devices show low subthreshold swing, which is due to good passivation of the Si-NC surface defect during the nitridation treatment. [17] After the erasing operation under a −7-V pulse voltage of 1 ms, the transfer characteristic curves of five kinds of test key cells are in good agreement with each other. After the programming operation under +7 V pulse voltage of 1 ms, the transfer characteristic curves are also in good agreement with each other.…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…In our previous work, we reported that the surface-nitrided Si-NC NVM devices show low subthreshold swing, which is due to good passivation of the Si-NC surface defect during the nitridation treatment. [17] After the erasing operation under a −7-V pulse voltage of 1 ms, the transfer characteristic curves of five kinds of test key cells are in good agreement with each other. After the programming operation under +7 V pulse voltage of 1 ms, the transfer characteristic curves are also in good agreement with each other.…”
Section: Methodssupporting
confidence: 60%
“…The details of sample fabrication can be found in our previous work. [17] As listed in Table 1, eight kinds of test key cells with different gate widths and lengths are defined. The topographic-view AFM, SEM images, and statistic size distribution for Si-NCs are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1990 [1], silicon quantum dots (Si QDs) have been intensively studied because of the possibility of applications such as compatible metal-oxide-semiconductor (CMOS) devices [2], light source [3][4][5], fluorescent tags for biomedical applications [6], and their novel applications with electrical and optical functions. For accomplishment of various applications, we need to be trying to understand how to control the size of Si QD embedded in an insulating layer.…”
Section: Introductionmentioning
confidence: 99%
“…Group IV quantum dots (QDs) are attractive for non-volatile memories (NVMs) considering their compatibility with CMOS technology [1][2][3][4][5][6][7][8][9][10]. Additionally, QDs can tune NVM device parameters related to performance and stability by tailoring their size, density, and interface quality with embedding oxide [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%